The generation and forecasting of escalation indices for capital cost estimating in the petro-chemical industry, with special emphasis on the cost indices for major equipment - Conradie, Alexander Floris (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1986.